CuO-doped TiO2 nanofiber catalyst as well as preparation method and application thereof

By preparing CuO-doped TiO2 nanofiber membranes, the problems of difficult recycling and narrow light response range of traditional TiO2 photocatalysts were solved, and efficient photocatalytic performance and simple recycling in the visible light region were achieved, making it suitable for photocatalytic degradation and hydrogen production reactions.

CN120714631APending Publication Date: 2025-09-30新疆理工学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510957325.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Traditional TiO2 photocatalysts are difficult to recycle, have a narrow light response range, and are prone to secondary pollution. In addition, fiber membrane catalysts are prone to agglomeration, have few active sites, and have a small specific surface area.

Method used

CuO-doped TiO2 nanofiber membrane was prepared by electrospinning. Tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone were mixed, electrospun, impregnated with copper nitrate solution and calcined to form CuO-doped TiO2 nanofiber catalyst.

Benefits of technology

The light absorption range is extended to the visible light region, which improves the utilization rate of sunlight. The catalyst can be recovered by simple filtration, which reduces operating costs and the risk of secondary pollution. It is suitable for photocatalytic degradation of pollutants and light-driven reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120714631A_ABST
    Figure CN120714631A_ABST
Patent Text Reader

Abstract

The invention provides a CuO-doped TiO2 nanofiber catalyst as well as a preparation method and application thereof, and belongs to the technical field of photocatalytic materials. The preparation method comprises the following steps: mixing tetrabutyl titanate, an ethanol solution, an acetic acid solution and polyvinylpyrrolidone, and carrying out electrostatic spinning to obtain a TiO2 fiber membrane; mixing copper nitrate with water to obtain a copper nitrate impregnation liquid; and placing the TiO2 fiber membrane in a copper nitrate impregnation liquid, impregnating, and calcining to obtain the CuO-doped TiO2 nanofiber catalyst. The nanofiber catalyst prepared by the preparation method disclosed by the invention can expand a light absorption range to a visible light region, greatly improves the utilization rate of visible light, and is suitable for a reaction of producing hydrogen by photolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a CuO-doped TiO2 nanofiber catalyst and a preparation method and application thereof. Background Art

[0002] As an abundant element and versatile energy carrier, hydrogen is an ideal clean energy source for the future. Among existing hydrogen production methods, photocatalytic water splitting is the most promising and clean method. Traditional photocatalytic hydrogen production catalysts are mostly in powder form. During photocatalytic water splitting, fiber membrane catalysts are prone to agglomeration, have few active sites, and have a small specific surface area. They are easily dispersed in the liquid phase, difficult to recover, and cause environmental pollution. Traditional TiO2 photocatalysts also have problems such as a small visible light response range, difficulty in recovering the powder after the hydrogen production process, and the tendency to cause secondary pollution. Summary of the Invention

[0003] The purpose of the present invention is to provide a CuO-doped TiO2 nanofiber membrane catalyst and its preparation method and application, so as to solve the problems of traditional TiO2 being difficult to recycle and having a narrow light response range.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a CuO-doped TiO2 nanofiber catalyst, comprising the following steps: (1) Tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone were mixed and electrospun to obtain a TiO2 fiber membrane; (2) mixing copper nitrate and water to obtain a copper nitrate impregnation solution; (3) The TiO2 fiber membrane is placed in a copper nitrate impregnation solution, impregnated and calcined to obtain a CuO-doped TiO2 nanofiber catalyst.

[0005] Preferably, the concentration of the ethanol solution in step (1) is 17-18 mol / L, and the concentration of the acetic acid solution is 17-18 mol / L.

[0006] Preferably, the mass ratio of tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone in step (1) is 11-12:4-5:3-4:1.

[0007] Preferably, the mixing temperature in step (1) is 15-25° C., the mixing time is 1-24 h, and the mixing stirring rate is 350-800 r / min.

[0008] Preferably, the voltage of the electrospinning in step (1) is 12-25 kV, the translation speed of the electrospinning spinneret is 0.1-1 mL / h, the translation stroke of the electrospinning is 300-500 mm, the vertical distance between the electrospinning spinneret and the collecting drum is 12-25 cm, and the rotation speed of the collecting drum is 80-350 r / min.

[0009] Preferably, the concentration of the copper nitrate impregnation solution in step (2) is 2-20%.

[0010] Preferably, the mass ratio of the TiO2 fiber membrane to copper nitrate in step (3) is 1:0.1-1.27.

[0011] Preferably, the calcination temperature in step (3) is 300-500° C., and the calcination time is 3-6 hours.

[0012] The present invention also provides a CuO-doped TiO2 nanofiber catalyst prepared by the method for preparing the CuO-doped TiO2 nanofiber catalyst.

[0013] The present invention also provides the use of the CuO-doped TiO2 nanofiber catalyst in photocatalytic materials.

[0014] The present invention has the following beneficial effects: The present invention provides a method for preparing a CuO-doped TiO2 nanofiber catalyst, comprising the following steps: (1) mixing tetrabutyl titanate, an ethanol solution, an acetic acid solution and polyvinyl pyrrolidone, and performing electrostatic spinning to obtain a TiO2 fiber membrane; (2) mixing copper nitrate and water to obtain a copper nitrate impregnation solution; and (3) placing the TiO2 fiber membrane in the copper nitrate impregnation solution, performing impregnation and calcination to obtain a CuO-doped TiO2 nanofiber catalyst.

[0015] The nanofiber catalyst prepared by the preparation method of the present invention can extend the light absorption range to the visible light region, greatly improving the utilization rate of sunlight, and is suitable for photocatalytic degradation of pollutants or light-driven reactions.

[0016] The macroscopic bulk structure of the nanofiber catalyst obtained by the present invention avoids the problem of difficult separation of traditional nanofiber membrane catalysts and can be recovered by simple filtration or sedimentation, thereby reducing the operating costs and secondary pollution risks in industrial applications.

[0017] The raw materials used in the present invention are all low-cost, low-toxic materials. They can improve catalytic performance while taking sustainable development into consideration, making them suitable for large-scale environmental remediation and energy conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1XRD patterns of CuO-doped TiO2 nanofiber catalysts and TiO2 nanofiber membranes prepared in Examples 1-5; Figure 2 Infrared spectra of the CuO-doped TiO2 nanofiber catalyst and TiO2 nanofiber membrane prepared in Examples 1-5.

[0019] Figure 3 This is a line chart of photocatalytic hydrogen production of CuO-doped TiO2 nanofiber catalysts and TiO2 nanofiber membranes prepared in Examples 1-5.

[0020] Figure 4 This is a bar chart of photocatalytic hydrogen production of CuO-doped TiO2 nanofiber catalysts and TiO2 nanofiber membranes prepared in Examples 1-5. DETAILED DESCRIPTION

[0021] The present invention provides a method for preparing a CuO-doped TiO2 nanofiber catalyst, comprising the following steps: (1) Tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone were mixed and electrospun to obtain a TiO2 fiber membrane; (2) mixing copper nitrate and water to obtain a copper nitrate impregnation solution; (3) The TiO2 fiber membrane is placed in a copper nitrate impregnation solution, impregnated and calcined to obtain a CuO-doped TiO2 nanofiber catalyst.

[0022] In the present invention, the concentration of the ethanol solution in step (1) is preferably 17-18 mol / L, more preferably 17.2 mol / L, and the concentration of the acetic acid solution is preferably 17-18 mol / L, more preferably 17.5 mol / L.

[0023] In the present invention, the mass ratio of tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone in step (1) is preferably 11-12:4-5:3-4:1, and more preferably 11.8:4.2:3.4:1.

[0024] In the present invention, the mixing temperature in step (1) is preferably 15-25°C, more preferably 18-20°C, the mixing time is preferably 1-24h, more preferably 5-20h, and the mixing stirring rate is preferably 350-800r / min, more preferably 380-750r / min.

[0025] In the present invention, the electrospinning in step (1) is performed using a syringe. The size of the syringe is preferably 1-20 mL, more preferably 5-15 mL, the inner diameter of the needle in the syringe is preferably 0.39-0.43 mm, more preferably 0.4-0.42 mm, the outer diameter of the needle in the syringe is preferably 0.58-0.75 mm, more preferably 0.62-0.69 mm, and the injection speed of the syringe is preferably 0.2-0.5 mm / min, more preferably 0.25-0.45 mm / min.

[0026] In the present invention, the voltage of the electrospinning in step (1) is preferably 12-25 kV, more preferably 14-22 kV, the translation speed of the electrospinning spinneret is preferably 0.1-1 mL / h, more preferably 0.2-0.8 mL / h, the translation stroke of the electrospinning is preferably 300-500 mm, more preferably 320-480 m, the vertical distance between the electrospinning spinneret and the collecting drum is preferably 12-25 cm, more preferably 14-22 cm, and the rotation speed of the collecting drum is preferably 80-350 r / min, more preferably 90-330 r / min.

[0027] In the present invention, the concentration of the copper nitrate impregnation solution in step (2) is preferably 2-20%, more preferably 2%, 5%, 10%, 15% and 20%.

[0028] In the present invention, the mass ratio of the TiO2 fiber membrane to copper nitrate in step (3) is preferably 1:0.1-1.27.

[0029] In the present invention, the calcination temperature in step (3) is preferably 300-500°C, more preferably 350-480°C, and the calcination time is preferably 3-6h, more preferably 3.5-4.8h.

[0030] The present invention also provides a CuO-doped TiO2 nanofiber catalyst prepared by the preparation method of the CuO-doped TiO2 nanofiber catalyst.

[0031] The present invention also provides the use of CuO-doped TiO2 nanofiber catalyst in photocatalytic materials.

[0032] In the present invention, unless otherwise specified, the raw materials required for preparation are all commercially available products well known to those skilled in the art.

[0033] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention. Example

[0034] (1) 11.8 g of tetrabutyl titanate, 4.2 g of a 17.2 mol / L ethanol solution, 3.4 g of a 17.5 mol / L acetic acid solution, and 1 g of polyvinyl pyrrolidone were stirred at 450 r / min for 8 h at 15°C to obtain a spinning solution. A 10 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution and electrospin to obtain a TiO2 fiber membrane.

[0035] The parameters of the above-mentioned electrospinning are as follows: the electrospinning voltage is 18 kV, the injection speed is 0.4 mm / min, the receiving device is covered with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 120 r / min, the electrospinning spinneret translation speed is preferably 0.5 mL / h, the electrospinning translation stroke is 450 mm, the spinning temperature is 25°C, and the relative humidity is 35%.

[0036] (2) Mix 0.2 g of copper nitrate with 10 mL of water to obtain a 2% copper nitrate impregnation solution.

[0037] (3) After placing 1 g of TiO2 nanofiber membrane in the above-mentioned copper nitrate impregnation solution, it was calcined at 500 °C for 4 h to obtain CuO-doped TiO2 nanofiber catalyst, which was recorded as 2% / CuO@TiO2.

[0038] The nanofiber membrane catalyst obtained in this example can produce hydrogen at a rate of 45-50 μmol·h for photolysis of water. -1 ·g -1 .

[0039] The degradation rate of wastewater containing methylene blue using the nanofiber membrane catalyst obtained in this example is above 98%. Example

[0040] (1) 11.8 g of tetrabutyl titanate, 4.2 g of a 17.2 mol / L ethanol solution, 3.4 g of a 17.5 mol / L acetic acid solution, and 1 g of polyvinyl pyrrolidone were stirred at 450 r / min for 8 h at 15°C to obtain a spinning solution. A 10 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution and electrospin to obtain a TiO2 fiber membrane.

[0041] The parameters of the above-mentioned electrospinning are as follows: the electrospinning voltage is 18 kV, the injection speed is 0.4 mm / min, the receiving device is covered with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 120 r / min, the electrospinning spinneret translation speed is preferably 0.5 mL / h, the electrospinning translation stroke is 450 mm, the spinning temperature is 25°C, and the relative humidity is 35%.

[0042] (2) Mix 0.5 g of copper nitrate with 10 mL of water to obtain a 5% copper nitrate impregnation solution.

[0043] (3) After placing 1 g of TiO2 nanofiber membrane in the above-mentioned copper nitrate impregnation solution, it was calcined at 500 °C for 4 h to obtain CuO-doped TiO2 nanofiber catalyst, which was recorded as 5% / CuO@TiO2. Example

[0044] (1) 11.8 g of tetrabutyl titanate, 4.2 g of a 17.2 mol / L ethanol solution, 3.4 g of a 17.5 mol / L acetic acid solution, and 1 g of polyvinyl pyrrolidone were stirred at 450 r / min for 8 h at 15°C to obtain a spinning solution. A 10 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution and electrospin to obtain a TiO2 fiber membrane, designated as 10% / CuO@TiO2.

[0045] The parameters of the above-mentioned electrospinning are as follows: the electrospinning voltage is 18 kV, the injection speed is 0.4 mm / min, the receiving device is covered with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 120 r / min, the electrospinning spinneret translation speed is preferably 0.5 mL / h, the electrospinning translation stroke is 450 mm, the spinning temperature is 25°C, and the relative humidity is 35%.

[0046] (2) Mix 1 g of copper nitrate with 10 mL of water to obtain a 10% copper nitrate impregnation solution.

[0047] (3) After placing 1 g of TiO2 nanofiber membrane in the above-mentioned copper nitrate impregnation solution, it was calcined at 500 °C for 4 h to obtain CuO-doped TiO2 nanofiber catalyst, which was recorded as 10% / CuO@TiO2. Example

[0048] (1) 11.8 g of tetrabutyl titanate, 4.2 g of a 17.2 mol / L ethanol solution, 3.4 g of a 17.5 mol / L acetic acid solution, and 1 g of polyvinyl pyrrolidone were stirred at 450 r / min for 8 h at 15°C to obtain a spinning solution. A 10 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution and electrospin to obtain a TiO2 fiber membrane.

[0049] The parameters of the above-mentioned electrospinning are as follows: the electrospinning voltage is 18 kV, the injection speed is 0.4 mm / min, the receiving device is covered with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 120 r / min, the electrospinning spinneret translation speed is preferably 0.5 mL / h, the electrospinning translation stroke is 450 mm, the spinning temperature is 25°C, and the relative humidity is 35%.

[0050] (2) Mix 1.5 g of copper nitrate with 10 mL of water to obtain a 15% copper nitrate impregnation solution.

[0051] (3) After placing 1 g of TiO2 nanofiber membrane in the above-mentioned copper nitrate impregnation solution, it was calcined at 500 °C for 4 h to obtain CuO-doped TiO2 nanofiber catalyst, which was recorded as 15% / CuO@TiO2. Example

[0052] (1) 11.8 g of tetrabutyl titanate, 4.2 g of a 17.2 mol / L ethanol solution, 3.4 g of a 17.5 mol / L acetic acid solution, and 1 g of polyvinyl pyrrolidone were stirred at 450 r / min for 8 h at 15°C to obtain a spinning solution. A 10 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution and electrospin to obtain a TiO2 fiber membrane.

[0053] The parameters of the above-mentioned electrospinning are as follows: the electrospinning voltage is 18 kV, the injection speed is 0.4 mm / min, the receiving device is covered with aluminum foil on the receiving roller, the vertical distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 120 r / min, the electrospinning spinneret translation speed is preferably 0.5 mL / h, the electrospinning translation stroke is 450 mm, the spinning temperature is 25°C, and the relative humidity is 35%.

[0054] (2) Mix 2 g of copper nitrate with 10 mL of water to obtain a 20% copper nitrate impregnation solution.

[0055] (3) After placing 1 g of TiO2 nanofiber membrane in the above-mentioned copper nitrate impregnation solution, it was calcined at 500 °C for 4 h to obtain CuO-doped TiO2 nanofiber catalyst, which was recorded as 20% / CuO@TiO2.

[0056] Performance Testing The above examples 1-5 and TiO2 nanofiber membrane were subjected to XRD test, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen Figure 1 The XRD patterns of TiO2 nanofiber membranes and composites with different contents of CuO@TiO2 show that no new diffraction peaks appear when comparing the characteristic peaks of TiO2 nanofiber membranes. 2% CuO@TiO2, 5% CuO@TiO2, 10% CuO@TiO2, 15% CuO@TiO2, and 20% CuO@TiO2 indicate that doping with CuO does not destroy the crystal structure of the TiO2 nanofiber membrane. However, when the CuO concentration is 20%, characteristic peaks of CuO appear at 2θ=35.555 (red line) and 38.75 (blue line), confirming that CuO is successfully doped on the surface of the TiO2 nanofiber membrane.

[0057] The above examples 1-5 were subjected to infrared spectroscopy analysis and testing with TiO2 nanofiber membranes. Figure 2 As shown. Figure 2 It can be seen that the structure of the catalyst was characterized by Fourier transform infrared spectroscopy (FT-IR), and the results showed that there was obvious hydroxyl characteristic absorption on the surface of the sample. Figure 2 As shown, 3300cm -1 The broad band at 1650 cm-1 can be attributed to the stretching vibration behavior of the surface hydroxyl (-OH). -1 (C=O bond) and 2800cm -1 New characteristic absorption peaks appear at the C-H bond. The signals of these organic functional groups may come from the organic residues introduced during the preparation process. -1 The characteristic absorption bands observed in the range correspond to the typical vibration modes of Ti-O-Ti and Ti-O bonds in the TiO2 lattice.

[0058] The above Examples 1-5 were tested for photocatalytic hydrogen production with TiO2 nanofiber membranes. The photocatalytic hydrogen production test process is as follows: Accurately weigh 30 mg of the catalyst prepared in Examples 1-5 and the TiO2 nanofiber membrane into a 50 mL beaker. A mixture of 10 mL of anhydrous ethanol and 10 mL of ultrapure water was added as a sacrificial agent, stirred thoroughly, and then transferred to an AR80 chain-type clamp reactor. A vacuum pump was activated to continuously evacuate the reaction chamber until the solution interface was stable and bubble-free, ensuring complete removal of air from the system. A circulating cooling system was used to maintain a constant temperature of 5°C to minimize the effects of photothermal effects on the reaction. The vertical distance between the xenon lamp source and the liquid surface was adjusted to 10 cm to ensure uniform light intensity distribution. A PLS-SEX300 xenon lamp (full spectrum output, 320-780 nm) was activated, along with a Labsolar-6A system. A programmed sampling mode was set, with a reaction time of 30 minutes and five cycles. Gas samples were quantitatively analyzed using a GC 2002 gas chromatograph. The cumulative hydrogen volume and the corresponding amount of hydrogen produced by photolysis of water were calculated based on the integrated area of ​​the characteristic hydrogen peaks and a calibration standard curve.

[0059] The photocatalytic water splitting hydrogen production evaluation platform used in this experiment was jointly provided by Shanghai Kechuang Instrument Co., Ltd. and Beijing Perfect Light Technology Co., Ltd. It consists of a photocatalytic reaction unit, a gas collection unit, and a gas detection unit. The system employed a 250 mL AR80 chain-type sandwich reactor equipped with an O-ring seal and a quartz window. It was paired with a PLS-SEX300 xenon lamp light source system, which boasts a 300 W output power and covers the 320-780 nm (UV-Vis) emission spectrum. It was also equipped with a Labsolar-6A fully automated gas collection workstation (6A system) and a GC 2002 gas chromatograph, using 99.999% ultrahigh-purity argon as the carrier gas. During operation, the system was programmed to perform automatic gas sampling and detection in a 30-minute cycle.

[0060] The line graph of the above-mentioned photocatalytic hydrogen production is as follows: Figure 3 As shown, the bar chart is Figure 4 As shown. Figure 3 It can be seen that the hydrogen production performance of pure TiO2 nanofiber membrane is only 35 μmol·g -1 ·h -1 , the hydrogen production performance is significantly improved after doping with CuO. Figure 4 The hydrogen production capacity of 2%CuO@TiO2, 5%CuO@TiO2, 10%CuO@TiO2, 15%CuO@TiO2 and 20%CuO@TiO2 nanofiber membranes was 89 μmol·g -1 ·h -1 , 182 μmol·g -1 ·h -1 , 222 μmol·g -1 ·h -1 , 294 μmol·g-1 ·h -1 、656μmol·g -1 ·h -1 Among them, 20% CuO@TiO2 has the best photocatalytic hydrogen production performance, which is 18 times higher than that of pure TiO2 nanofiber membrane.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing CuO-doped TiO2 nanofiber catalyst, characterized in that: The impregnation method of doping CuO includes the following steps: (1) Tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone were mixed and electrospun to obtain a TiO2 fiber membrane; (2) mixing copper nitrate and water to obtain a copper nitrate impregnation solution; (3) The TiO2 fiber membrane is placed in a copper nitrate impregnation solution, impregnated and calcined to obtain a CuO-doped TiO2 nanofiber catalyst.

2. The method for preparing CuO-doped TiO2 nanofiber catalyst according to claim 1, characterized in that: The concentration of the ethanol solution in step (1) is 17-18 mol / L, and the concentration of the acetic acid solution is 17-18 mol / L.

3. The method for preparing CuO-doped TiO2 nanofiber catalyst according to claim 1, characterized in that: The mass ratio of tetrabutyl titanate, ethanol solution, acetic acid solution and polyvinyl pyrrolidone in step (1) is 11-12:4-5:3-4:

1.

4. The method for preparing the CuO-doped TiO2 nanofiber catalyst according to claim 1, wherein: The mixing temperature in step (1) is 15-25° C., the mixing time is 1-24 h, and the mixing stirring rate is 350-800 r / min.

5. The method for preparing CuO-doped TiO2 nanofiber catalyst according to claim 1, characterized in that: The voltage of the electrospinning in step (1) is 12-25 kV, the translation speed of the electrospinning spinneret is 0.1-1 mL / h, the translation stroke of the electrospinning is 300-500 mm, the vertical distance between the electrospinning spinneret and the collecting drum is 12-25 cm, and the rotation speed of the collecting drum is 80-350 r / min.

6. The method for preparing CuO-doped TiO2 nanofiber catalyst according to claim 1, characterized in that: The concentration of the copper nitrate impregnation solution in step (2) is 2-20%.

7. The method for preparing CuO-doped TiO2 nanofiber catalyst according to claim 1, characterized in that: The mass ratio of the TiO2 fiber membrane to copper nitrate in step (3) is 1:0.1-1.

27.

8. The method for preparing CuO-doped TiO2 nanofiber catalyst according to claim 1, characterized in that: The calcination temperature in step (3) is 300-500°C, and the calcination time is 3-6 hours.

9. The CuO-doped TiO2 nanofiber catalyst prepared by the method for preparing the CuO-doped TiO2 nanofiber catalyst according to any one of claims 1 to 8.

10. Use of the CuO-doped TiO2 nanofiber catalyst according to claim 9 in photocatalytic materials.